Substrate distribution in fungus chambers in nests of Atta bisphaerica Forel, 1908 (Hym., Formicidae) - Moreira, A. A.; Forti, Luiz Carlos [UNESP]; Boaretto, MAC; Andrade, APP; Rossi, M. N. (Blackwell Verlag Gmbh, 2003)
Substrate distribution was studied in three adult colonies of the leaf-cutting ant Atta bisphaerica Forel, 1908 using dye. Some supply holes were mapped using baits made from small plastic straws impregnated with citric pulp. Two holes, equidistant from one another, were then selected in each nest. The colonies were excavated completely 24 h after bait placement. During excavation, fungus chambers were checked for dye. We observed that the dyed baits were distributed in all sectors and at all depths regardless of where the baits had been placed. This supported the hypothesis that toxic baits placed in a single supply hole are uniformly distributed throughout the colony.